"If Everything is Stable, One is Not Going To Move Very Far": Reality as Illusion in Ondaatje’s The Cat’s Table - Barratt, Jessica Kristie (MacEwan University Student eJournal, 2014)
This essay examines one of the major themes of Michael Ondaatje’s The Cat’s Table: Perception and Reality. While on the surface the novel is about a young boy on a journey, it is Michael’s unique perspective that reveals an elusive truth about our reality: that it is a fragile illusion, at best. Via a comparison of Michael’s past (specifically the twenty-one days he was aboard a ship named Oronsay) and present realities, then, both Michael and the reader come to realize the highly subjective nature of our collective ’reality.’